2022
DOI: 10.1111/ijd.16203
|View full text |Cite
|
Sign up to set email alerts
|

Possible interaction between eosinophils and other immune cells in the pathomechanism of eosinophilic pustular folliculitis

Abstract: Possible interaction between eosinophils and other immune cells in the pathomechanism of eosinophilic pustular folliculitis Dear Editor, A 49-year-old man with a history of diffuse large B-cell lymphoma (DLBCL) was referred to us for exacerbation of atopic dermatitis (AD). He was diagnosed with DLBCL at the age of 46 years. He received CHASER therapy (cyclophosphamide, etoposide, cytarabine, dexamethasone sodium phosphate, and rituximab) for recurrent DLBCL lesions in the liver, lung,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…7 The classic EPF lesions appear as follicular papular pustules on an erythematous base, 1 to 2 mm in diameter, and extend eccentrically around in a circular or creeping pattern for 7 to 10 days, alternating between self-remission and exacerbation, and recurring once every 3 to 4 weeks. 8 A few patients may present early with symmetrical butterfly-shaped erythema of the face without papules or pustules, which is difficult to distinguish from lupus erythematosus, and three of our ten patients presented with this manifestation (Figure 1A, D and G). EPF lesions tend to occur on the face, trunk, and upper extremities, with rashes also appearing on the scalp and lower extremities, occasionally involving the lip mucosa, and 20% of rashes have been reported to involve the palmoplantar region.…”
Section: Discussionmentioning
confidence: 77%
“…7 The classic EPF lesions appear as follicular papular pustules on an erythematous base, 1 to 2 mm in diameter, and extend eccentrically around in a circular or creeping pattern for 7 to 10 days, alternating between self-remission and exacerbation, and recurring once every 3 to 4 weeks. 8 A few patients may present early with symmetrical butterfly-shaped erythema of the face without papules or pustules, which is difficult to distinguish from lupus erythematosus, and three of our ten patients presented with this manifestation (Figure 1A, D and G). EPF lesions tend to occur on the face, trunk, and upper extremities, with rashes also appearing on the scalp and lower extremities, occasionally involving the lip mucosa, and 20% of rashes have been reported to involve the palmoplantar region.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have suggested a relationship between classic EPF and sebum overproduction and sex hormones, while others propose an abnormal response to saprophytic microorganisms. 8 The typical skin lesions of classic EPF are localized on the upper limbs’ face, trunk, and extensor surfaces. They present as pruritic annular or serpiginous plaques with follicular papules and pustules, expanding outward while regressing centrally.…”
Section: Discussionmentioning
confidence: 99%